2013
DOI: 10.1371/journal.pone.0080751
|View full text |Cite
|
Sign up to set email alerts
|

Novel Factors in the Pathogenesis of Psoriasis and Potential Drug Candidates Are Found with Systems Biology Approach

Abstract: Psoriasis is a multifactorial inflammatory skin disease characterized by increased proliferation of keratinocytes, activation of immune cells and susceptibility to metabolic syndrome. Systems biology approach makes it possible to reveal novel important factors in the pathogenesis of the disease. Protein-protein, protein-DNA, merged (containing both protein-protein and protein-DNA interactions) and chemical-protein interaction networks were constructed consisting of differentially expressed genes (DEG) between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 111 publications
(120 reference statements)
1
24
0
1
Order By: Relevance
“…fibronectin have been implicated in psoriasis pathogenesis. Application of large-scale gene expression studies extended our knowledge regarding molecular abnormalities in involved and non-involved epidermis [14][15][16][17][18][19]. Recent RNA-Sequencing-based experiments have indicated that a large number of mRNAs are consistently differentially expressed in healthy and involved skin samples across independent studies, at both the transcript and gene levels [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…fibronectin have been implicated in psoriasis pathogenesis. Application of large-scale gene expression studies extended our knowledge regarding molecular abnormalities in involved and non-involved epidermis [14][15][16][17][18][19]. Recent RNA-Sequencing-based experiments have indicated that a large number of mRNAs are consistently differentially expressed in healthy and involved skin samples across independent studies, at both the transcript and gene levels [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Concerning the role of associated metabolic diseases, Manczinger and Kèmeny used such a network based on a protein-protein interaction databank (STING) and chemical interaction databank (STITCH). Although further experimental validation is needed, they revealed a role of PI3KR1 in the psoriasis interaction network [29]. This protein was previously shown to play a role in insulin resistance [30] adding further evidence to the observed differential metabolic disease pathways in psoriasis.…”
Section: Emerging Technologiesmentioning
confidence: 90%
“…Assessing the network of expressed transcription factors may provide information about the cellular infiltrate and the respective polarization (e.g., Th1-T-bet) [24,45]. Network construction can also be used to expose protein-protein interactions or to predict a potential drug effect based on publicly available datasets as described by Manczinger and Kèmeny [29] and others [44,46]. Ultimately, to gain biologically relevant insights via high-throughput methods, considering genomic information in the course of the data analysis is indispensable and reveals relevant DNA motifs/"psoriasis responsive elements".…”
Section: Ups and Downs Of Skin Molecular Profilingmentioning
confidence: 99%
“…Likewise, in skin substitutes, cytokine-induced gene expression modulation is in agreement with induction of psoriasis-like changes (increase in DEFB4A, CXCL3 and IL-8, and decrease in HPGD). In addition, there were increases in markers of psoriatic epithelium (HAS3, SERPINB1, CTGF [23][24][25] ) and decreases in markers of epithelial differentiation (KRT10, FLG). In the psoriasiform skin substitutes, bakusylan lowered the expression of six psoriasis-related genes, including STAT3 and the proinflammatory, irritation-related cytokines IL-8 and CXCL3, which, by contrast, were unfavourably upregulated by ATRA and adapalene (ADP) (IL-8) and tazarotene (TAZ) (CXCL3).…”
Section: Effect Of Bakusylan On Psoriasis-surrogate Human Epidermal Kmentioning
confidence: 99%